2023
DOI: 10.3390/cancers15030912
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Growth Models of Breast Cancer for Evaluating Early Detection—A Summary and a Simulation Study

Abstract: With the advent of nationwide mammography screening programmes, a number of natural history models of breast cancers have been developed and used to assess the effects of screening. The first half of this article provides an overview of a class of these models and describes how they can be used to study latent processes of tumour progression from observational data. The second half of the article describes a simulation study which applies a continuous growth model to illustrate how effects of extending the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Therefore, we should be cautious with interpreting the results, since some of the predicted screen‐detected cases are overdiagnosed 47 . One approach to study this is to use these models in a broader simulation, as we have previously outlined 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we should be cautious with interpreting the results, since some of the predicted screen‐detected cases are overdiagnosed 47 . One approach to study this is to use these models in a broader simulation, as we have previously outlined 48 …”
Section: Discussionmentioning
confidence: 99%
“…47 One approach to study this is to use these models in a broader simulation, as we have previously outlined. 48 The modeling approach used in this new risk prediction relies heavily on its parametric assumptions. They are necessary to piece together the latent natural history based only on data from diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overdiagnosis, the proportion of breast cancers that would not have been diagnosed during a woman's lifetime in absence of screening, is considered to be one of the largest harms of screening [ 7 ]. Estimates of overdiagnosis vary largely (0%–91%) and depend on many factors, such as whether the estimate includes only IBC, only DCIS, or both [ 5 , 7 , [9] , [10] , [11] ]. Although there is consensus that DCIS is the largest contributor to overdiagnosis, the extent to which this occurs is unclear due to the unknown natural history of DCIS [ 3 , 6 , 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modelling studies provide a complementary method to make accurate estimates of tumour progression and overdiagnosis, with their ability to use long follow-up and account for both the benefits and harms of screening. Especially natural history models can provide insight into underlying processes and can be useful in assessment of the benefits and harms of screening scenarios [ 11 ]. However, modelling studies have shown a large range in assumptions that affect tumour progression and overdiagnosis estimates [ 2 , 3 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation